Impact of Digital Ecosytem, Technological Innovations, Renewable Energy Consumption and Financial Development on CO₂ Emissions in Pakistan (Journal of Asian Development Studies, 2025)
This study examines the impact of the digital ecosystem, technological innovations, renewable energy consumption, and financial development on CO₂ emissions in Pakistan. As environmental sustainability becomes a global priority, understanding the role of digital transformation and technological advancements in mitigating carbon emissions is crucial. Using time-series data of 30 years (1994 to 2023) and applying econometric techniques like ARDL, the study explores how digitalization and technological progress influence environmental quality, while also assessing the contribution of renewable energy adoption and financial development in reducing emissions. The findings reveal that a digital ecosystem enhances CO₂ emission in Pakistan due to enhanced energy consumption and production through traditional energy sources. Surprisingly technological innovations also have negative impact on CO₂ emission. In developed countries like Pakistan, technological innovations have positive impact on environment. The possible reason for this negative relation is low investment in R&D and green technologies. Additionally, increased renewable energy consumption significantly reduces environmental degradation. However, the relationship between financial development and emissions is complex, indicating that financial expansion must be aligned with green investment policies. The study highlights policy implications for fostering a sustainable economy through digitalization, clean energy transition, and green financing.